International Liver Transplant Society Practice Guidelines: Diagnosis and Management of Hepatopulmonary Syndrome and Portopulmonary Hypertension. Issue 7 (July 2016) - Krowka, Michael J.; Fallon, Michael B.; Kawut, Steven M.; Fuhrmann, Valentin; Heimbach, Julie K.; Ramsay, Michael A. E.; Sitbon, Olivier; Sokol, Ronald J.
Abstract : Abstract: Two distinct pulmonary vascular disorders, hepatopulmonary syndrome (HPS) and portopulmonary hypertension (POPH) may occur as a consequence of hepatic parenchymal or vascular abnormalities. HPS and POPH have major clinical implications for liver transplantation. A European Respiratory Society Task Force on Pulmonary-Hepatic Disorders convened in 2002 to standardize the diagnosis and guide management of these disorders. These International Liver Transplant Society diagnostic and management guidelines are based on that task force consensus and should continue to evolve as clinical experience dictates. Based on a review of over 1000 published HPS and POPH articles identified via a MEDLINE search (1985-2015), clinical guidelines were based on, selected single care reports, small series, registries, databases, and expert opinion. The paucity of randomized, controlled trials in either of these disorders was noted. Guidelines are presented in 5 parts; I. Definitions/Diagnostic criteria; II. Hepatopulmonary syndrome; III. Portopulmonary hypertension; IV. Implications for liver transplantation; and V. Suggestions for future clinical research. Abstract : Practice guideline for the management of Hepatopulmonary Syndrome and Portopulmonary Hypertension are set forth in this publication. The work is comprehensive and reflects current best practice and an international consensus.